Operando raman gradient analysis for temperature-dependent electrolyte characterization - Olbrich, LF; Jagger, B; Ihli, J; Pasta, M (American Chemical Society, 2024)
Transport and thermodynamic properties are integral parameters to understand, model, and optimize state-of-the-art and next-generation battery electrolytes. The accurate measurement of these properties is experimentally challenging as well as time- and resource-intensive, and consequently, reports are scarce. Their dependence on temperature is explored even less and is commonly limited to a few temperature points. Recently, we introduced an operando Raman gradient analysis (ORGA) tool to extract transport and thermodynamic properties. Here, we expand the capabilities of ORGA by incorporating a temperature-sensitive external reference into the design. With this enhancement, we are able to visualize the local concentration of any Raman-active species in the electrolyte and detect lithium filament nucleation. We demonstrate and validate this new functionality of ORGA via an examination of lithium bis(fluorosulfonyl)imide (LiFSI) in tetraethylene glycol dimethyl ether (G4) as a function of temperature. All transport properties and activation energies are reported, and the effect of temperature is discussed.